Water Pollution Analysis in Yogyakarta Special Region In 2019 - Nenik Santika; Diah Lutfi W (AIBPM Publisher, 2021)
The environment and natural resources are inputs in economic activities that have an impact on economic growth. On the other hand, economic activity can cause economic externalities. One form of environmental pollution is water pollution. Water pollution is a change in conditions in a water reservoir such as lakes, rivers, oceans and groundwater due to human activities. WHO (2019) globally, 15% of patients experience disease infections due to polluted water? Furthermore, WHO (2019) stated that around 829,000 people are estimated to die every year due to diarrhea and of them 297,000 children under 5 years old die from consuming unhealthy drinking water. The purpose of this study was to analyze water pollution in the Province of the Special Region of Yogyakarta (DIY) Indonesia. The research method used is a descriptive qualitative approach, the selection of this method aims to analyze the situation descriptively about the water quality index in DIY. The results showed that the water quality index of the Special Region of Yogyakarta was 38.43 or entered the alert category. The rivers in DIY in 2019 that have an alert category are Gajahwong, Kuning, Conteng, Belik, and Bulus. The policy implication that can be done is tightening the regulation of river functions.